Efectividad de la terapia de reprocesamiento por movimientos oculares, en el tratamiento de personas adultas con estrés postraumático. - Chicaiza Yauli, Lesly Isabel (2024)
The objective of this research work was to evaluate the effectiveness of eye movement reprocessing therapy (EMDR) in the treatment of adults with post-traumatic stress disorder (PTSD). The research corresponds to a bibliographic review, cross-sectional design and descriptive level. Where a non-probabilistic sample was used that is composed of 57 documents intentionally selected from a total of 916 scientific articles and documents published between 2014 and 2024 in journals indexed in databases recognized at a global, regional and national level, accounts such as PubMed, Science Direct, ProQuest, Springer Publishing, Taylor & Francis Online, among others. Methodological quality is guaranteed through the application of CRF-QS instruments. Regarding the results, the effectiveness of EMDR therapy in reducing PTSD symptoms was evidenced, although its effectiveness may vary depending on the clinical context and individual characteristics of the patients. Compared to other treatments, EMDR therapy showed high effectiveness in reducing symptoms in a short period of time, leading to an improvement in quality of life and a decrease in associated symptoms. In conclusion, according to the information collected, eye movement reprocessing therapy is effective for the treatment of adults suffering from posttraumatic stress disorder.